Domestic investment, external debt and economic growth: cointegration and causality evidence from Nigeria - Adamu Ibrahim Mohammed, Rasiah Rajah (Universiti Pendidikan Sultan Idris, 2017)
Domestic investment, external debt and economic growth: cointegration and causality evidence from Nigeria by Adamu Ibrahim Mohammed, Rasiah Rajah,